A Convenção nº 169 da Organização Internacional do Trabalho sobre direitos indígenas e sua (in)aplicabilidade no território brasileiro - Souza Júnior, Ângelo Aparecido de (2016)
The Brazilian Federal Constitution of 1988 brought great changes concerning the treatment of indigenous peoples, especially the principle of alterity, reflecting on the right for the indigenous people to be different, as well as the issues on indigenous lands, which have some of very own institutes, diverse from Brazilian Civilian Law. However, it has not always been this way. Brazil has been through many legislation evolutions until we reached the current moment, when the integrationist idea relating the indigenous people to the local society has lost its power and has now disappeared, after the 1988 Constitution. We started with the investigation of the existence or not of an indigenous estate inside the Brazilian territory before the European colonization that justifies the primary rights to the lands that they traditionally occupy, provided by our Federal Constitution. To corroborate the need for a better protection to the indigenous people, we studied the International Conventions, which were held around this subject, especially the ones edited by the International Labour Organization (ILO), which asks for a detailed analysis on the organization and its juridical capacity of International Law to be part of a treaty. Therefore, considering the referred International Conventions endorsed by Brazil, we could observe the concern in the International scenery about the indigenous people. Notwithstanding the endorsement by Brazil, it is necessary to analyze the process of internalization of these, considering the dualist and unitary tendencies; the status of these conventions when they get to Brazil; and the eventuality of some constitutional habit. We also searched in the infra-constitutional legislation, if it presents any irregular habit with the Federal Constitution and if they contribute to a better perception of the importance of the protection of the indigenous peoples as a mechanism of preservation of the social organization, customs, languages, beliefs and traditions of these peoples.